A Case of Prenatal Diagnosis of Congenital Total AV Block on VSD and PDA with Ultrasound - Yusrawati, Yusrawati; Wahdini, Nanda Tri; Rasyid, Hauda El; Riendra, Muhammad (Andalas Obstetrics And Gynecology Journal, 2021)
Objective : To report the diagnosis and management of congenital total AV block on VSD and PDA in pregnancy.Method : A case reportCase : A 37-year-old multiparous woman G4P3A0H2 24- 25 weeks of preterm pregnancy with fetal bradycardia, VSD, PDA with ultrasonography and CTG results was FHR 70 bpm. At 37- 38 weeks of pregnancy, termination of pregnancy was performed by cesarean delivery with preparation for complication of fetal AV block. A male baby was born with weight 2600 gram and APGAR score of 8/9. Immediate echocardiography result was situs solitus, VSD PM LR shunt, PDA LR shunt, good left ventricular function, left aortic arch and EF 74%. ECG result was sinus bradycardia, total AV block with junctional escape rhythm. Sternotomy and PPM implantation was performed by cardiothoracic surgeon three hours after the baby was born. Post PPM implantation, ECG results was HR 165 bpm and chest X- rays interpretation was cardiomegaly with plethora. Mother and baby came home in good condition on the 6th day of treatment. On the next baby’s control at 4.5 months obtained a weight of 5.4 kg with the echocardiography results was solitus, VSD PM LàR shunt, VSD muscular multiple 3 pieces LàR shunt, PDA LàR shunt, good right and left ventricular function, and left arch. The child got captopril 2x1.5 mg and planned for a 6-month repeat echocardiography.Conclusion : Congenital of total AV block on VSD and PDA is confirmed by prenatal diagnosis and preparation for comprehensive multidisciplinary management.Keywords: congenital total AV block, fetal bradycardia, fetal echocardiography, PPM, ultrasound